Evaluating compliance with process‐related quality metrics and survival in oral cavity squamous cell carcinoma: Multi‐institutional oral cavity collaboration study. Issue 1 (12th September 2020) - Liu, Sara W.; Woody, Neil M.; Wei, Wei; Appachi, Swathi; Contrera, Kevin J.; Tsai, Jillian C.; Ghanem, Ahmed I.; Matia, Brian; Joshi, Nikhil P.; Geiger, Jessica L.; Ku, Jamie A.; Burkey, Brian B.; et al.
Abstract: Background: Process‐related measures have been proposed as quality metrics in head and neck cancer care. A recent single‐institution study identified four key metrics associated with increased survival. This study sought to validate the association of these quality metrics with survival in a multi‐institutional cohort. Methods: Multicenter retrospective study of patients with oral cavity squamous cell (1/2005‐1/2015). Baseline patient and disease characteristics and compliance with quality metrics was evaluated. Association between compliance with quality metrics with overall survival (OS), disease‐free survival (DFS), and disease‐specific survival (DSS) was evaluated using Cox proportional hazards models. Results: Failure to comply with two or more of the quality metrics was associated with worse OS, DFS, and DSS. Adherence to all or all but one of the quality metrics was found to be associated with improved survival. Conclusions: Process‐related quality metrics are associated with increased survival in patients with oral cavity squamous cell carcinoma in a multi‐institutional cohort.